PENGARUH JENIS BAMBU DAN UKURAN PARTIKEL TERHADAP SIFAT FISIK PAPAN SEMEN - M Loiwatu; Viktor Kewilaa; Olga Nataly da Costa (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2019)
Objective of the study was to measure effect of bamboo species and the types of particles to the physical properties of cement board. Type of wood particles used in cement board were sawdust, flake, and mixture of flake and sawdust. Factorial experiment in randomized complete design was applied in the study with two factors such as species of bamboo (Dendrocalamus asper, Backe), (Gigantochloa atter (Hask) Kurz ex Munro) and (Bambussa vertilatta), and type of wood particles (sawdust, flake, and mixture of flake and sawdust). Result of the study indicated that types of wood particles was highly significant effect to the cement board such as density of board in oven dry condition and air dry condition. Combination of species of bamboo and types of wood particles was significant effect to the thickness swelling of the board. Species of bamboo was not significant effect to physical properties of the board.